History, Classification, Molecular Structure and Properties of Dendrimers which are a New Concept in Textile - Osman NAMIRTI; Rıza Atav (Pamukkale University Journal of Engineering Sciences, 2011)
Over the last 20 years polymer chemistry has created a number of non-lineer structures and introduction of a large number of branches during the polymer synthesis leads to obtain molecules with many end groups. Two types of these polymers are regularly branched "dendrimers" and "hyperbranched polymers" where branching is formed randomly. In this article knowledge about history, classification, molecular structure and properties of dendrimers which have found various application areas also in textile due to their special structures is given.